Longitudinal resting state fMRI analysis in healthy controls and premanifest Huntington's disease gene carriers: A three‐year follow‐up study. Issue 1 (19th August 2014) - Odish, Omar F.F.; van den Berg‐Huysmans, Annette A.; van den Bogaard, Simon J.A.; Dumas, Eve M.; Hart, Ellen P.; Rombouts, Serge A.R.B.; van der Grond, Jeroen; Roos, Raymund A.C.; on behalf of the TRACK‐HD Investigator Group
Abstract Background: We previously demonstrated that in the premanifest stage of Huntington's disease (preHD), a reduced functional connectivity exists compared to healthy controls. In the current study, we look at possible changes in functional connectivity occurring longitudinally over a period of 3 years, with the aim of assessing the potential usefulness of this technique as a biomarker for disease progression in preHD. Methods: Twenty‐two preHD and 17 healthy control subjects completed resting state functional magnetic resonance imaging (fMRI) scans in two visits with 3 years in between. Differences in resting state connectivity were examined for eight networks of interest using FSL with three different analysis types: a dual regression method, region of interest approach, and an independent component analysis. To evaluate a possible combined effect of gray matter volume change and the change in blood oxygenation level dependent signal, the analysis was performed with and without voxel‐wise correction for gray matter volume. To evaluate possible correlations between functional connectivity change and the predicted time to disease onset, the preHD group was classed as preHD‐A if ≥10.9 years and preHD‐B if <10.9 years from predicted disease onset. Possible correlations between burden of pathology score and functional connectivity change in preHD were also assessed. Finally, longitudinal change in whole brain and striatal volumetric measures was assessed in the studied cohort. Results: Longitudinal analysis of the resting state‐fMRI (RS‐fMRI) data revealed no differences in the degree of connectivity change between the groups over a period of 3 years, though a significantly higher rate of striatal atrophy was found in the preHD group compared to controls in the same period. Discussion: Based on the results found in this study, the provisional conclusion is that RS‐fMRI lacks sensitivity in detecting changes in functional connectivity in HD gene carriers prior to disease manifestation over a 3‐year follow‐up period. Hum Brain Mapp, 36:110–119, 2015. © 2014 Wiley Periodicals, Inc.